STRATEGI MANAJEMEN KESISWAAN RELIGIUS DALAM INTERNALISASI AKHLAK SISWA DI ERA DIGITAL: STUDI KASUS DI MTS NW MENGGALA - Lalu Ahyadi; Iskandar Abdurrahman; Maswir; Siti Inganah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology presents challenges for madrasahs in fostering students’ akhlak. This study aims to analyze religious student management strategies in the internalization of students’ akhlak in the digital era at MTs NW Menggala. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving the vice principal for student affairs, teachers, and students. The findings reveal four main strategies of akhlak internalization: religious habituation, dialogic discipline, role modeling, and extracurricular activities. The Vice Principal for Student Affairs plays a central role in planning, coordinating, implementing, and evaluating these programs. Supporting factors include a strong religious school culture and collaboration between the madrasah and families, while the main obstacles are parental supervision, environmental influences, and uncontrolled digital media exposure. The study concludes that religious student management serves as a strategic approach to internalizing students’ akhlak through systematic and sustainable educational practices in the digital era.